2022
DOI: 10.2147/jir.s372449
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Severe Eosinophilic Esophagitis and Multi-Organ Inflammation by Airborne Allergens is Associated with IL-4/IL-13 and CCL11 but Not IgE in Genetic Susceptible Mice

Abstract: Background Eosinophilic Esophagitis (EoE) is an increasingly common chronic inflammatory disease. The pathological mechanisms underlying EoE are largely unknown. Objective We sought to understand the mechanisms underlying aeroallergen-induced EoE in Sharpin gene deficient (Sharpin-/-) mice that is prone to inflammatory response. Methods Sharpin-/-mice were exposed with Aspergillus fumigatus and ovalbumin intranasall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recently, a causal relationship between oral immunotherapy (OIT) to food allergens and the development of EoE has also been proven. A role for inhaled allergens in both the onset and exacerbation of EoE seems less certain but possible, as suggested by a study that showed an association between pollen season and the incidence of diagnosis and the timing of EoE exacerbations [7]. The development and exacerbation of EoE by inhaled allergens through a cross-reactivity mechanism with food allergens is also thought to be potentially possible [7].…”
Section: Eosinophilic Oesophagitis -Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a causal relationship between oral immunotherapy (OIT) to food allergens and the development of EoE has also been proven. A role for inhaled allergens in both the onset and exacerbation of EoE seems less certain but possible, as suggested by a study that showed an association between pollen season and the incidence of diagnosis and the timing of EoE exacerbations [7]. The development and exacerbation of EoE by inhaled allergens through a cross-reactivity mechanism with food allergens is also thought to be potentially possible [7].…”
Section: Eosinophilic Oesophagitis -Aetiologymentioning
confidence: 99%
“…A role for inhaled allergens in both the onset and exacerbation of EoE seems less certain but possible, as suggested by a study that showed an association between pollen season and the incidence of diagnosis and the timing of EoE exacerbations [7]. The development and exacerbation of EoE by inhaled allergens through a cross-reactivity mechanism with food allergens is also thought to be potentially possible [7]. Recent studies have also increasingly suggested the possibility of EoE following sublingual immunotherapy for respiratory allergies.…”
Section: Eosinophilic Oesophagitis -Aetiologymentioning
confidence: 99%